The implementation of School Literature Movement in West Lombok Regency, West Nusa Tenggara Province â Indonesia: an Exploratory Study - Soepriyanti, Henny; Waluyo, Untung; Sujana, Made; Arifuddin, Arifuddin (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Responding to studentsâ low-ranking achievements in the Program for International Student Assessment (PISA), Minister of Education and Culture of Indonesia introduced a School Literacy Movement (SLM) to schools in an effort to improve studentsâ reading competence. Despite such an effort, the implementation of SLM in schools still undergoes hurdles. The present study aims to (a) investigate how SLM is implemented in junior high schools in West Lombok Regency; (b) identify the good practice of SLM; (c) promote models of evaluation that supports the implementation of SLM. The research employed a qualitative research method. Data were collected through interviews, observations and questionnaires from 10 junior high state schools in West Lombok Regency. Results of the study show thin schools employed different approaches to the implementation of SLM due to unavailability of clear guidance to run SLM. Also, schools did not have evaluation tools to assess studentsâ reading competence.